Assessment of Pregnant Women Knowledge toward Urinary Tract Infection in Primary Health Care Centers at Kirkuk City - Mohammad, Manar; AL- Saffar, Fatin (Iraqi National Journal of Nursing Specialties, 2018)
Abstract Objective: To assess pregnant women Knowledge toward Urinary Tract Infection at Kirkuk City.Methodology: A descriptive and analytical study was conducted from 1st of November 2013 and up to the 19 th of August 2014 in five typical primary health care centers at Kirkuk City. A Probability (randomly sample) was used to select the sample of 180 women aged (15-44) years. A questionnaire format was used as a tool for data collection , content validity of the questionnaire achieved through reviewing it by (24) experts in numerous scientific fields and reliability of the questionnaire was determined through a pilot study. Descriptive and inferential statistics were used to analyze the data. Results : The results of the study revealed that most of the study sample (31.1%) & (31.1%) were in age groups ( 20-24) & (25-29) years respectively, with Mean ± SD (29.2 ±1.33) years. Nearly one third of them ( 32.2%) were primary school graduates , (83.3%) were housewives, the vast majority (98.8%) were livining in urban areas , and (65%) were from low socioeconomic class. Assessment of women's knowledge about UTI , the results reported '' inadequate knowledge '' for most UTI knowledge categories including: 1.General information about UTI , 2. Causes, Mode of transmission, Complications , Investigation. While '' adequate knowledge '' of women for the following categories : 1.Sign &symptoms of UTI , 2. Treatment, 3. Prevention.